Respuesta :

Answer:

      x = (-9 + 2i√6)/12    and (-9 - 2i√6)/12

Step-by-step explanation:

"Finding zeroes" means find the x-values that make f(x) = 0, so we have...

0 = 6x² + 12x - 7

Use quadratic equation to solve...

x = [-12 ± √(12² - 4(6)(-7))]/[2(6)]

   

    x = [-12 ± √(144 + 168)]/12

 

        x = [-9 ± √-24]/12  

***√-24 becomes (√24)(√-1) which becomes (√4)(√6)(√-1),

√-1 = i, so this simplifies to 2i√6

            x = [-9 ± 2i√6]/12

                  x = (-9 + 2i√6)/12    and (-9 - 2i√6)/12

                     

ACCESS MORE